The effects of the "vestibular sedative" drug, Flunarizine upon the vestibular and oculomotor systems. Issue 8 (August 1983) - Ell, J; Gresty, M
Abstract : The effects of the "vestibular sedative" drug Flunarizine upon the oculomotor functions of pursuit and voluntary saccades and upon the vestibular response (to rotational stimuli) were assessed in twenty volunteer subjects. The study was then extended to three patients with chronic imbalance of central origin who had reported a beneficial symptomatic response to the drug. Three of the volunteer subjects were found to have a directional preponderance (presumed to arise from peripheral dysfunction). In the remaining seventeen normal subjects Flunarizine was found to reduce the amplitudes of fast phases of vestibular nystagmus. The directional preponderance in the other three subjects was redressed through production of fast phases which were of lower and more uniform amplitude. In the patients, in addition to a reduction in fast phase amplitude, there was a reduction or abolition of after nystagmus. In no case was any reduction in slow phase velocity observed. Pursuit and voluntary saccades were unaffected by the drug. It was concluded, on the basis that the fast phases of nystagmus are centrally generated, that Flunarizine has a central action rather than a depressant effect upon the vestibular end organ. In view of known oculomotor physiology and pharmacology it is proposed that vestibular sedatives act by depression of Type II vestibular neurons, and modification of the functional relationships between the vestibular nuclei, the perihypoglossal nuclei and the flocculus of the cerebellum. A trial of vestibular active drug is indicated particularly in patients in whom asymmetry of the vestibular response and/or abnormal after nystagmus is demonstrated.